Observing young children’s play: a brief review - Gökce, Kurt (Gyermeknevelés Tudományos Folyóirat, 2019)
<span style="color: #000000; font-family: Roboto-Regular, Helvetica, Arial, sans-serif; font-size: 15px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The observational techniques are significant tools to inform educational practice and research. Thanks to their advantage of providing authentic data, these techniques are vastly used to inform theory and practice in the field of early childhood education and development. In this brief review; (1) the observational methods, (2) the observational settings, (3) the types of observations, (4) the observational tools, and (5) the ethical considerations have been delineated in the context of educational research and practice.